Evaluation of Some Intestinal Biomarkers in the Determination of Intestinal Damage in Calves with Coccidiosis - M. K. Durgut; M. Ok (Faculty of Animal Science, Bogor Agricultural University, 2023)
This study aimed to assess the usefulness of injury biomarkers specific to the intestines in identifying the presence and degree of intestinal epithelial damage in coccidiosis-infected calves. Forty calves of various breeds and sexes, aged 21 days to 60 days, were used in the study. Of these, 30 were in the experimental group, and 10 were healthy control. The McMaster Oocyte counting technique was used to diagnose Eimeria and confirm clinical coccidiosis. Cases with clinical signs and more than 5,000 oocysts in gram feces were included in the study. All calves had blood samples drawn at the 0th hours and 72nd hours. Blood gas measurements were performed with a blood gas analyzer. Hemogram was performed with an automated hematologic analyzer. Bovine-specific enzyme-linked immunosorbent analysis (ELISA) test kits were used to measure the intestinal fatty acid binding protein (I-FABP), trefoil factor-3 (TFF-3), intestinal alkaline phosphatase (IAP), claudin-3 (CLD-3), intestinal smooth muscle actin (ACTG2), and interleukin-8 (IL-8) biomarkers from serum samples. Calves with coccidiosis received a single dose of toltrazuril (15 mg/kg) and supportive care. Before treatment (0th hours) in coccidiosis-infected calves, serum I-FABP and CLD-3 levels were greater than in healthy calves (p<0.05), and after treatment (72nd hours), serum TFF-3 and ACTG2 levels were higher than in healthy calves. There was a significant decrease in serum IL-8 levels in coccidiosis-infected calves after treatment (72nd hours) compared to pre-treatment (0th hours) (p<0.05). I-FABP, TFF-3, CLD-3, ACTG2, and IL-8 are helpful and reliable biomarkers that can be utilized to assess the presence of intestinal epithelium injury in coccidiosis-infected calves.